Jim Jarmusch: Musik und Narration: Transnationalität und alternative filmische Erzählformen - Feiten, Benedikt (transcript, 2017)
The role music plays in Jim Jarmusch`s transnational films: By using the aspects of repetition and variation, Benedikt Feiten presents new perspectives on alternative kinds of film narration.